Structure-Based Design of Porcine Circovirus Type 2 Chimeric VLPs (cVLPs) Displays Foreign Peptides on the Capsid Surface - Wang, Dongliang; Zhang, Sujiao; Zou, Yawen; Yu, Wanting; Jiang, Yifan; Zhan, Yang; Wang, Naidong; Dong, Yanpeng; Yang, Yi (Frontiers in Cellular and Infection Microbiology, 2018)
Although porcine circovirus-like particles can function as a vector to carry foreign peptides into host cells, displaying foreign peptides on the surface of virus-like particles (VLPs) remains challenging. In this study, a plateau, consisting of the middle portion of Loop CD (MP-Lcd) from two neighboring subunits of PCV2 capsid protein (Cap), was identified as an ideal site to insert various foreign peptides and display them on surface of PCV2 VLPs. Further, biological roles of MP-Lcd regarding VLPs assembly, cellular entry and antigenicity were investigated to determine whether this was a universal site for insertion of foreign functional peptides. Three-dimensional (3D) structure simulations and mutation assays revealed MP-Lcd was dispensable for PCV2 Cap assembly into VLPs and their entry into host cells. Notably, substitution of MP-Lcd with a foreign peptide, caused surface pattern changes around two-fold axes of PCV2 VLPs, but was not detrimental to VLPs assembly and cellular entry. Moreover, this substitution had no adverse effect on eliciting neutralizing antibodies (NAbs) against PCV2 infection in pigs. In conclusion, MP-Lcd of the PCV2 Cap was a promising site to accommodate and display foreign epitopes or functional peptides on the surface of PCV2 VLPs. Furthermore, chimeric VLPs (cVLPs) would have potential as bivalent or multivalent vaccines and carriers to deliver functional peptides to target cells.